Large-cell calcifying Sertoli cell tumour of the testis: Associated organ anomalies - (:unkn) unknown (My University, 1999)
A case is reported of unilateral, focal large-cell calcifying Sertoli cell tumour (LCCSCT) of the testis associated with complex endocrine disorders and cardiac myxomas. It is believed that there are two distinct groups of patients with this tumour: those who have complex dysplastic syndromes and bilateral and multifocal tumours; and those without any syndromes but who have unilateral and focal tumours. The presented case differs in that, although the patient has a unilateral focal tumour, unique organ anomalies, such as renal agenesis and inferior vena cava duplication, are also present. These anomalies with LCCSCT have not been reported before.
Keywords: Inferior vena cava duplication; Large-cell calcifying Sertoli cell tumour; Sertoli cell tumour; Testicular tumour